Metabolome and transcriptome profiling reveals light-induced anthocyanin biosynthesis and anthocyanin-related key transcription factors in Yam (Dioscorea Alata L.) - Peipei Zhang; Shiqiang Xu; Long Zhang; Xulong Li; Jie Qi; Lin Weng; Shike Cai; Jihua Wang (BMC Plant Biology)
Abstract Background Yam is a globally significant crop with both culinary and medicinal value. Anthocyanin, an important secondary metabolite, plays a key role in determining the nutritional quality of yams. However, the research on the light-induced anthocyanins accumulation in yams remains limited. In this study, we revealed light-induced anthocyanin biosynthesis and identified transcription factors associated with anthocyanin-related pathways in yam. These findings enhance our understanding of the molecular mechanisms underlying light-mediated anthocyanin regulation in yams. Results Significant variations in color were observed in the stems, leaves, and tuber roots of the two yam varieties ‘Xuwen’ and ‘Luhe’. Under light conditions, the total anthocyanin content in ‘Xuwen’ tuber roots was significantly higher than that under dark conditions. The targeted metabolomics analysis of anthocyanins identified that procyanidin and cyanidin glycosides, such as cyanidin-3-O-(sinapoyl)sophoroside, cyanidin-3-O-sophoroside, procyanidin B1, procyanidin B3, and quercetin-3-O-glucoside, were the primary anthocyanin components. These compounds were responsible for the observed differences in anthocyanin content between the two varieties and were significantly influenced by light conditions. The non-targeted metabolomics analysis further revealed that light also induce the biosynthesis of flavonoids. Transcriptome analysis showed significant differences in the expression levels of MYB, ERF, and WRKY transcription factors (TFs) between the two yam varieties, with these expressions being strongly influenced by light conditions. The association analysis of the anthocyanin metabolome, candidate TFs, and structural genes involved in anthocyanin biosynthesis revealed significant correlations. Specifically, MYB (Dioal.09G044700 and Dioal.12G068700) and WRKY (Dioal.20G040900 and Dioal.12G062900) showed strong correlations with procyanidins, anthocyanins, and the structural genes associated with anthocyanin biosynthesis. RT-qPCR confirmed that the expression patterns of these four TFs, strongly induced by light, were consistent with the expression of structural genes involved in anthocyanin biosynthesis. Conclusions The results of this study provide useful insights into the regulation of light on anthocyanin accumulation in yam, and will be helpful for yam breeding and cultivation practices.